Internalization of Escherichia coli O157:H7 gfp+ in rocket and Swiss chard baby leaves as affected by abiotic and biotic damage. (1st July 2017) - Hartmann, R.; Fricke, A.; Stützel, H.; Mansourian, S.; Dekker, T.; Wohanka, W.; Alsanius, B.
Abstract: Internalization of human pathogens in edible parts of vegetables eaten raw is a major concern, since once internalized they are protected from sanitizing treatments. In this study, we examined the invasion of gfp ‐labelled Escherichia coli O157:H7 into intact and biotically (infection with Xanthomonas campestris / Pseudomonas syringae ) and abiotically (grating with silicon carbide) damaged leaves of wild rocket ( Diplotaxis tenuifolia ) and Swiss chard ( Beta vulgaris subsp. cicla ) using laser scanning confocal microscopy. Bacterial cells were found in internal locations of the tissue, irrespective of tissue health status. Contaminated leaf sections of biotically and abiotically damaged wild rocket leaves showed higher susceptibility to microbial invasion, while the pathogen was internalized in greater numbers into intact Swiss chard leaf sections when abiotically, but not biotically, damaged. The greatest differences were observed between the plant species; after surface sanitization, E. coli O157:H7 was still detected in wild rocket leaves, but not in Swiss chard leaves. Significance and Impact of the Study: Contamination of leafy vegetables with Escherichia coli O157:H7 is a growing problem, as reported outbreaks are increasing. However, establishment of this human pathogen in the phyllosphere is not completely understood. Using laser scanning confocal microscopy, we demonstrated that E. coli O157:H7 gfp+ can invade plant tissue of Swiss chard and wild rocket leaves and that the bacterium is more sensitive to surface sanitization of Swiss chard leaves. Damage to leaf tissue promoted leaf invasion, but the nature of the damage (abiotic or biotic) and plant species had an impact.